الإمام الكلاباذي وزياداته في كتابه "معاني الأخبار" على الكتب الستة: جمعا ودراسة تخريجية - مري، سعيد سالم
This research aimed to study the book "Bahr al- Fawa'id' known as 'Ma'ani al-Akhbar' authored by Imam al-Kilabadhi (may Allah have mercy on him) as a critical study of 'Kutb al-Sittah' (the renown six Hadeeth books). The book, 'Bahr al-Fawa'id' compiled by its author with chains of transmission traceable to the messenger of Allah (may the peace and prayer be upon him) may either agree (in their chains of transmission) with the compilations of the authors of 'Kutb al-Sittah' or may be unique to them. The researcher came across some Hadeeths which are only narrated in the aforementioned book and thus saw the need to investigate their chains of transmission. As for those Hadeeths in the book which are in agreement with the 'Kutb al-Sittah', a great attention has been paid on them by the scholars who have conducted studies on the Kutb al-Sittah and there is no need to repeat the same work that have been repeatedly done. However, this study aimed at securitizing the non-conforming Hadeeths with Kutb al-Sittah in the aforementioned book which no one has previously securitized in solitude. In order to achieve this objective, the researcher employed an inductive approach in collecting the focused Hadeeths. He then adopted a critical approach in criticizing and screening out those that sound from the weak. The research found that some of these Hadeeths are authentic, some are perfect. Some were also found to be slightly weak, some are very weak, while the rest are fabricated ones. The researcher then substantiates the results of the study by the sayings of the scholars of Hadeeth criticism. At times, he might agree with the scholars who have passed a ruling on a Hadeeth, while he might disagree with them at other times. This kind of scrutiny is based on the evidence surrounding each Hadeeth, and it was found that Imam Alkilabadhi did not rule on those Hadeeths, but merely reported them with their chains of transmission and this is not enough.